Unraveling Child Legal Problems in the Era of the Covid-19 Pandemic in a Holistic Paradigm Perspective - Bambang Sukoco; Moh. Indra Bangsawan Indra; Dewi Eko Wati; Dewi Kusuma Diarti; Sandya Mahendra; Arnold Tri Hantoro (Universitas Muhammadiyah Surakarta, 2023)
The legal approach (Law No. 35 of 2014 concerning Child Protection) in solving problems related to child protection during the Covid-19 pandemic has not shown optimal results so that an alternative approach is through a holistic approach that will elaborate on the relationship between law and other scientists. Objective: This research aims to: 1). Describe a holistic paradigm from a legal perspective; 2). Describe the concept of a holistic paradigm as an effort to protect children from acts of family-based violence during the Covid-19 pandemic. Methods: This research is normative legal research with a statutory approach and a holistic concept approach. Findings: A holistic approach in law means reinstatement the law with its environment; by reuniting it with society’s realities, it will restore the integrity of the law itself. A holistic approach to child protection in the Covid-19 pandemic era can be learnt in several aspects, namely religious aspects, health aspects, psychological aspects, sociological aspects, economic aspects and legal aspects. Function: This research explains the urgency of the holistic concept that regulates child protection, which means recombining the law with its environment. Novelty: There has not been any research that studies the same topic as that discussed in this article